Analysis Of Pre-Service and In-Service Teachers’ Perceptions About Practical Activities Involving Remote Laboratory - Girotto Júnior, Gildo Girotto; Cachichi, Ricardo Cenamo; Galembeck, Eduardo; Muniz Vazquez , Pedro Antônio (Góndola, enseñanza y aprendizaje de las ciencias, 2022)
The use of information and communication technologies in education and teacher training is a topic investigated in various areas of knowledge. Recognizing aspects related to pedagogical problematization using specific technologies beyond the technical use of resources in pedagogical practices has also been a concern in this ​​research area. In this scenario, the Remote Laboratories present tools that can contribute to developing experimental practices, incorporating technologies that contribute to the student's scientific education. This work investigates the perceptions of chemistry students and science teachers regarding an activity that involves a practical activity in the Remote Laboratory. Data collection was using questionnaires, analyzed qualitatively through the Discursive Textual Analysis technique. Results show positive perceptions about this type of laboratory in terms of its versatility to face real problems and in environments with few resources and possibilities for pedagogical actions aimed at working with active methodologies, promoting student participation. Most of the negative perceptions refer to aspects that are not directly related to the remote laboratory but are associated with the investigative nature of the activity. Some perceptions refer to topics to be improved, such as the delay in the experiment transmission. It was possible to promote a process of reflection on the use of these resources.